The Multifaceted Impact of Mindfulness on Chronic Diseases: A Comprehensive Review of Its Relationship with Diabetes Mellitus, Hypertension, Insomnia, Obesity, Gastrointestinal Disorders, and Migraine - Ismael, Mazen (J Med Rehab Sci, 2025)
Mindfulness has emerged as a holistic approach that enhances psychological well-being and physiological functioning. This comprehensive review explores the relationship between mindfulness and major chronic conditions, including Diabetes Mellitus (DM), Hypertension (HTN), Insomnia, Obesity, Gastrointestinal Disorders (such as Irritable Bowel Syndrome and Inflammatory Bowel Disease), and Migraine. Evidence suggests that mindfulness-based interventions (MBIs) significantly improve disease management and quality of life across various patient populations. The review highlights recent randomized controlled trials, systematic reviews, and meta-analyses to provide an updated synthesis of the impact of mindfulness on symptom severity, metabolic parameters, inflammatory markers, and behavioral outcomes. Furthermore, the paper discusses underlying mechanisms, clinical implications, and future research directions, emphasizing mindfulness as an integrative strategy in chronic disease prevention and treatment. In particular, this review aims to explore recent innovations in mindfulness-based interventions—including digital delivery, VR applications, and condition-specific adaptations—as well as examine the contributing psychosomatic, behavioral, and physiological causes linking chronic disease with psychological distress.